2020
DOI: 10.1186/s12939-020-01189-1
|View full text |Cite
|
Sign up to set email alerts
|

A distributional regression approach to income-related inequality of health in Australia

Abstract: Background: Several studies have confirmed the existence of a significant positive relationship between income and health. Conventional regression techniques such as Ordinary Least Squares only help identify the effect of the covariates on the mean of the health variable. In this way, important information of the income-health relationship could be overlooked. As an alternative, we apply and compare unconventional regression techniques. Methods: We adopt a distributional approach because we want to allow the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Besides, recent studies that extended the conventional regression approaches in evaluating the health effects of income using distributional regressions techniques found that households with poor income are particularly faced with more significant health risks. Also, they are at the lower end of the health distribution (see Kessels, Hoornweg, Thanh Bui, & Erreygers, 2020 ; Silbersdorff, Lynch, Klasen, & Kneib, 2018 ). Using the health and income distribution data in 2019, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, recent studies that extended the conventional regression approaches in evaluating the health effects of income using distributional regressions techniques found that households with poor income are particularly faced with more significant health risks. Also, they are at the lower end of the health distribution (see Kessels, Hoornweg, Thanh Bui, & Erreygers, 2020 ; Silbersdorff, Lynch, Klasen, & Kneib, 2018 ). Using the health and income distribution data in 2019, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the construction of the ICS, Pearson's correlation of 64 social indicators related to demography (13), education (10), sanitation (9), health (12), work (8), and vulnerability (12) with the preventable fetal mortality rate (Supplementary Material Chart 1). Indicators with p <0.05 remained in the process.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the relationship between socioeconomic conditions and public health problems, statistical models such as the Generalized Linear Models (GLM) have been used to model the mean of the response variable 7 , however many phenomena require that the modeling of other distribution parameters be considered 7 . Thus, the use of the framework for the Generalized Additive Models for Location, Scale and Shape (GAMLSS) stands out for allowing to model the response variable and to specify all its parameters as linear functions of a set of explanatory variables 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The call for evaluating effects that go beyond the mean of an outcome variable is certainly not new. Various previous studies in econometrics (Koenker & Bassett, 1978), psychology (Balota & Yap, 2011;Campitelli et al, 2017;Wiedermann & Alexandrowicz, 2007), education (Costanzo & Desimoni, 2017;Konstantopoulos et al, 2019;Petscher & Logan, 2014), and health sciences (Hart, 2001;Kessels et al, 2020;Rousselet et al, 2017) documented advantages of statistical methods that go beyond standard conditional mean-testing. In general, one can distinguish two approaches to modeling data beyond conditional means, distribution free models and complete distribution models (Kneib, 2013).…”
Section: Modeling Distributional Treatment Effectsmentioning
confidence: 99%